The targeted delivery of anti-metastasis oligonucleotide in breast cancer cells by the nanoliposomes conjugated with RGD ligand - Farahanaz Kavian Manesh; Ali Jebali; Flora Forouzesh (Advances in Cancer Biology - Metastasis)
To decrease the ETV4 gene, which is important in metastasis, the nanoliposome containing ETV4 antisense oligonucleotide conjugated with Arginylglycylaspartic acid (RGD) ligand was used in the study. The nanoliposome containing ETV4 antisense oligonucleotide conjugated with RGD ligand was synthesized and characterized by AFM, DLS, and FTIR. Then, MDA-MB-231, MCF-7, and MCF-10A cell lines were treated with different concentrations of nanoliposomes containing antisense ETV4 oligonucleotide conjugated with RGD, nanoliposomes without antisense ETV4 oligonucleotide, and antisense ETV4 oligonucleotide for 24 h. Finally, an MTT assay was used to evaluate cell viability, Real-time PCR was employed to assess the ETV4 mRNA expression, and western blotting was applied to evaluate the expression of ETV4 protein. Here, the characterization data revealed that the nanoliposome containing antisense ETV4 oligonucleotide conjugated with RGD had a spherical shape with a size range of 50–120 nm and zeta potential of −18mV to +7 mV. This study showed that although nanoliposomes containing antisense ETV4 oligonucleotide conjugated with RGD could effectively decrease the cell viability of MDA-MB-231 and MCF-7 cells, they could not dcrease cell viability of MCF-10A, indicating the effect of RGD ligand. Also, this novel carrier could decrease both mRNA and protein of the ETV4 gene in a dose dependent manner.